ANALISIS PERBANDINGAN HEDGING, SWAP CONTRACT DENGAN OPTION CONTRACT UNTUK MEMINIMALISASI KERUGIAN SELISIH KURS VALAS DALAM PEMBAYARAN HUTANG IMPORT - Zeinora Zeinora (JABE (Journal of Applied Business and Economic), 2016)
Investment activities  in Indonesia have an impact on domestic market foreign exchange activity which can be affect the fluctuation of  the exchange rate. In order to support the stability of the rupiah and as prudent step in ensuring the integrity and stability of financial corporation system have needs necessary steps to reduce pressure on the rupiah. Exchange rate fluctuation may also cause incertainty in the investment activity, so that hedging is a  need for investment activity. Hedging  is management risk technique by using derivatives or other hedging instruments to offset changes in fair value or cashflow changes in assets, liability, and future transactions. And effect of the hedge accounting is gain or loss on hedging instrument and the all item protects recocnized in the same period. In this case the author choose derivatives instrument  currency swap hedging with option contracthedging. This research aims to find  hedging method which review the lower debt payment among  swap contract  with option contract hedging. This study through literature,relevant research and publications related to the topic. Result of the study are expected to be a reference for development of international trade in Indonesia.